Applying the New Institute for Healthcare Improvement Inpatient Waste Tool to Identify "Waste" in the Intensive Care Unit. Issue 5 (September 2016) - Almoosa, Khalid F.; Luther, Katharine; Resar, Roger; Patel, Bela
Abstract : Abstract: Healthcare waste—the inappropriate use of healthcare resources that provides no benefit to patients yet contributes to cost and even harm—is a potentially significant contributor to high healthcare costs. This project aimed to apply a new locally modified Institute for Healthcare Improvement (IHI)–developed waste identification tool to measure the prevalence of and reason for the inappropriate use of intensive care unit (ICU) beds, one type of potential waste. Unnecessary days (i.e., waste) and their causes in a 16-bed "closed" medical ICU (MICU) and a 10-bed "semi-closed" transplant surgical ICU (TSICU) were identified by physicians over a 3-month period. Data on 513 patients admitted to both ICUs for a total of 1, 631 patient-days demonstrated that 15% of MICU days and 25.8% of TSICU days were unnecessary. Although causes of waste in each ICU differed, delays in transfer of patients out of the ICU, end-of-life decision-making, and delays in procedures were among the commonest. Determination of waste also varied among physicians, ranging from 4.5% to 27.7% in the MICU and 0%–37.5% in the TSICU. This study found that the IHI waste tool can be effectively used to identify waste in the ICU, which is common and varies based on the ICU type and physician perceptions.